Voltage control and virtual synchronous generator control of HVDC interconnection line for improving stability of power system including large‐scale wind farm - Ayaka Nakamura (Wiley, 2021)
Abstract Large‐scale integration of renewable energy sources (RESs) such as wind power can impact on the existing power system's stability. For example, there is a possibility that the wind farm (WF) cannot be maintained stable and then it is disconnected from the grid when the instantaneous voltage sag caused by a grid disturbance occurs. Moreover, the increasing integration of RESs in the power system can reduce the number of conventional synchronous generators (SGs) connected to the grid, and lead to a reduction of system inertia in the grid. The system inertia reduction can cause larger and faster frequency fluctuations during the transient period. Hence, this paper proposes a new control strategy composed of the voltage control for suppressing the voltage sag and the virtual synchronous generator (VSG) control based on the proportional‐integral‐differential (PID) fuzzy logic control (FLC) for maintaining the frequency stability which is performed by high voltage direct current (HVDC) interconnection line. The aim of the new control strategy is to improve the stability of the entire power system with large‐scale integration of RESs. The effectiveness of the proposed strategy is confirmed through the simulation analyses by PSCAD/EMTDC.